Exploring Lives of China Ming-Qing Female Poets: Collaboration of the "Ming-Qing Women’s Writings Digital Archive and Database" and the "China Biographical Database" - Hu, Jia-jia (Cultural and religious studies, 2017)
Based on the "Ming-Qing Women’s Writings (MQWW), a digital archive and database" project and the "China Biographical Database (CBDB)" project, which have been collaborating since 2008, this paper uses different digital methods to analyse the Ming-Qing women poets’ lives, such as the themes of their poems, their geographical distribution, and their social networks. The aim of this paper is to show researchers various prospects for the integration of digital humanities projects.